6y+16=2(4y+3)

Simple and best practice solution for 6y+16=2(4y+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y+16=2(4y+3) equation:


Simplifying
6y + 16 = 2(4y + 3)

Reorder the terms:
16 + 6y = 2(4y + 3)

Reorder the terms:
16 + 6y = 2(3 + 4y)
16 + 6y = (3 * 2 + 4y * 2)
16 + 6y = (6 + 8y)

Solving
16 + 6y = 6 + 8y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-8y' to each side of the equation.
16 + 6y + -8y = 6 + 8y + -8y

Combine like terms: 6y + -8y = -2y
16 + -2y = 6 + 8y + -8y

Combine like terms: 8y + -8y = 0
16 + -2y = 6 + 0
16 + -2y = 6

Add '-16' to each side of the equation.
16 + -16 + -2y = 6 + -16

Combine like terms: 16 + -16 = 0
0 + -2y = 6 + -16
-2y = 6 + -16

Combine like terms: 6 + -16 = -10
-2y = -10

Divide each side by '-2'.
y = 5

Simplifying
y = 5

See similar equations:

| x+1=9x^3+9x | | x+3y=120 | | 10s=5s+60 | | 17x-16=10x-63 | | x-3/2=-7 | | 400+50x=1400+10x | | 8(1-6x)-1=-8x-33 | | -5(2x-7)=11 | | x(x+7)=50 | | 3x+8+5x=5x-20 | | 19a-3(a-6)=663 | | 1/3(x+2)=12 | | -5x-x=2x-(4x+6) | | 12.50+2x=36.50 | | 2+2(8z-2)=5(5z+4)+3 | | 19a-3a-18=66 | | 13-2t+3t=-5-4 | | 6x-17=47+6x | | 2(5p-8)=-96 | | 5x-20+5x+4y=180 | | 2x+3=1x-7 | | 4b-8b=24 | | Y=X^3+15x^2+74x+120 | | y^2+45y-63=0 | | 1/2(6-a)=a | | 8x+17=-29+16x | | 8+-3=9 | | 3k-1= | | -6=5n+5+4 | | -3(-4x+5)=17 | | 15-4x=75 | | 4+8y=11y-17 |

Equations solver categories